Human Capital and Earnings: British Evidence and a Critique - Psacharopoulos, George; Layard, Richard (Review of Economic Studies, 1979)
Journal Article Human Capital and Earnings: British Evidence and a Critique Get access George Psacharopoulos, George Psacharopoulos London School of Economics Search for other works by this author on: Oxford Academic Google Scholar Richard Layard Richard Layard London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 3, July 1979, Pages 485–503, https://doi.org/10.2307/2297015 Published: 01 July 1979 Article history Received: 01 October 1976 Accepted: 01 June 1978 Published: 01 July 1979